Polydopamine surface-modified hyperbranched polymeric nanoparticles for synergistic chemo/photothermal therapy of oral cancer - Yin, Xingyong; Li, Zimu; Zhang, Yi; Zeng, Xiaowei; Wang, Qiuxu; Liang, Zhigang (Frontiers in Bioengineering and Biotechnology, 2023)
A novel drug delivery system for the treatment of oral cancer had been designed using a facile polydopamine (PDA)-based surface modification and a binding mechanism linking folic acid-targeting ligands. The system was capable of achieving the following objectives: loading of chemotherapeutic agents, active targeting, pH responsiveness and prolonged in vivo blood circulation. Polymeric nanoparticles loaded with DOX (DOX/H20-PLA@PDA NPs) were functionalized with amino-poly(ethylene glycol)-folic acid (H2N-PEG-FA) after coating with PDA to form the targeting combination, DOX/H20-PLA@PDA-PEG-FA NPs. The novel NPs exhibited similar drug delivery characteristics to DOX/H20-PLA@ PDA NPs. In the meanwhile, the incorporated H2N-PEG-FA contributed to active targeting, as illustrated in cellular uptake assays and animal studies. In vitro cytotoxicity and in vivo anti-tumor studies have shown that the novel nanoplatforms exhibit extremely effective therapeutic effects. In summary, the multifunctional PDA-modified H20-PLA@PDA-PEG-FA NPs offer a promising chemotherapeutic strategy to enhance the treatment of oral cancer.